Solve for k fk-gk=h

Math
fk-gk=h
Factor k out of fk-gk.
Tap for more steps…
Factor k out of fk.
kf-gk=h
Factor k out of -gk.
kf+k(-g)=h
Factor k out of kf+k(-g).
k(f-g)=h
k(f-g)=h
Divide each term by f-g and simplify.
Tap for more steps…
Divide each term in k(f-g)=h by f-g.
k(f-g)f-g=hf-g
Cancel the common factor of f-g.
Tap for more steps…
Cancel the common factor.
k(f-g)f-g=hf-g
Divide k by 1.
k=hf-g
k=hf-g
k=hf-g
Solve for k fk-gk=h

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top